POSITIVISM AND NATURAL LAW REVISITED - Legarre, Santiago (Prudentia Iuris, 2024)
March 2012 marked the time of my first of many visits from Argentina to the Notre Dame campus for purposes of teaching a mini-course at the Law School. In those days, Professor John Finnis used to come to South Bend forjust a few weeks of the Spring Semester, to teach a one-credit short course on Shakespeare. In 2012, as well as in several subsequent years, I timed my visits so as to overlap with this Spring visit of his. One night, over dinner, he told me that immediately before arriving in America he had been in Italy, where he had delivered a paper on Pope Benedict XVI’s speech at the Bundestag, in Berlin. When I was tasked by the Center for Ethics and Culture to comment, all these years later, on that Berlin speech, my mind went straight to thememory of that dinner.